Efektivitas Teknik Air Abrasion pada Preparasi Gigi terhadap Kekuatan Ikatan Resin Komposit (Laporan Penelitian) - Cinantya Putri Parahita; Ade Prijanti Dwisaptarini (Fakultas Kedokteran Gigi Universitas Trisakti, 2021)
ABSTRACTBackground:Minimal intervention dentistry promote the philosophy of prevention, remineralization, and minimal invasive in the practice of dentistry. One of the technique employed by this concept is air abrasion. Aim: to discover the effectiveness of air abrasion technique on the dental caries prepation towards the bond strength of composite resin with the method of scoping review. Method: This research utilize the PRISMA diagram, based on PubMed, PMC and Elsevier database with the keywords of: (((